KENYAMANAN BUS KOTA 01 SURAKARTA DITINJAU DARI ASPEK DESAIN INTERIOR (Studi Kasus Bus Kota Jalur Kartasura-Palur) - Agung Purnomo (Gelar : Jurnal Seni Budaya, 2010)
Not only does the discipline of interior design cover static interior such as houses and buildings,  but also dynamic interior like the interior of land, sea and air transportation. The interior design in  these two scopes must consider the comfort factor for the user besides the aesthetic aspect and  function. A city bus as a means of public transportation should take the comfort for the user into consideration as a public service. The interior condition of the city bus can indicate the comfort  and this can be seen from the condition of a space forming element, a space filler element, and  space layout. The object of this study is the interior of city buses in the direction of Kartasura-  Palur in Surakarta. The approach used is numerical quantitative, that is, a data analysis based on a quality realized in the form of numbers in atable to measure the level of comfort. The variables  measured cover: (1) the element of space forming (sub variable: floors, walls, and ceilings), (2) the element of space filler (sub variable: seats and supporting facilities) and (3) space condition  (sub variable: lighting, ventilation and acoustic). The population of this research is the entire fleet of a number of transportation company operating in Surakarta. The sample is taken using cluster random sampling, that is, covering all the companies of city bus in Surakarta consisting of PO Surya Kencana, PO Nusa, an Perum Damri. A check list is used to analyze the comfort level of the city bus in Surakarta. The result of the research showed that the comfort level of the city bus in Surakarta was still low assessed from the aspect of interior design. The space forming element has some shortcomings, among others, the material usage is not optimal and its condition is not  well maintained and even some have broken. The space forming element has also some shortcomings, for instance, 'the number of the seats does not meet the standard and some have broken. Besides that, the arrangement of other facilities is not well planned. The arrangement of space condition is not supported by proper ventilation, lighting and acoustic.                             Key words: comfort, city bus, and interior elements